Structural Behavior of Interlocking Load Bearing Hollow Block Wall Panels With Stiffeners Under In-Plane Vertical and Lateral Loads - Ali, Nisreen N. (2009)
An experimental study was conducted at the Universiti Putra Malaysia to investigate the effect of stiffeners on the structural behavior of Putra interlocking load bearing hollow block wall panels under vertical and lateral loadings. Putra block building system, developed by the Housing Research Centre of Universiti Putra Malaysia, consists of three types of blocks namely stretcher, corner and half blocks. Six wall panels each with 0.9 m width, 1.0 m height and 0.15 m thickness were tested. These wall panels were divided into two sets, each containing three specimens, one with no stiffener and the other two were stiffened with 2 and 3 steel bars and cement grout respectively. The steel bars were placed along the perimeter of the wall panels. All test specimens were subjected to in-plane loading. For vertical load test, uniformly distributed vertical load was applied from zero until failure. In lateral load test, a constant vertical load was applied on the top of the wall, while in-plane lateral load was applied from zero until failure. The effect of stiffeners was investigated by comparing important parameters such as; vertical deflection as well as in-plane and out of plane lateral deflections, failure loads and failure patterns between the stiffened and un-stiffened wall panels. To evaluate the resistances of the wall panels with different stiffeners, strength, cracks pattern and deformation were recorded and analyzed. The results show a significant increase in strength capacity associated with reduction in both lateral and vertical deflections for the stiffened wall panels. In addition, there was reduction in the in-plane lateral deflection for wall panels under the effect of lateral load. A significant change in crack pattern and failure mechanism was also observed. Compressive strength and shear strength for wall panels under the effect of vertical and lateral load which stiffened with 2 and 3 reinforcement steel bars were increased as compared with un-stiffened wall panel. The compressive strength was increased by 21% and 33% for wall panels stiffened with 2 and 3 reinforcement bars respectively as compared with un-stiffened wall panel. And, the shear strength was increased by 50% and 68.7% for wall panels stiffened with 2 and 3 reinforcement bars respectively as compared with un-stiffened wall panel.